PEMANFAATAN SAMPAH ORGANIK SEBAGAI BAHAN PUPUK CAIR UNTUK PERTUMBUHAN TANAMAN BAYAM MERAH (ALTERNANTHERA FICOIDES) - NURUL LATIFAH, RIRIS Nurul (LenteraBio: Berkala Ilmiah Biologi, 2012)
Waste of the market activity that does not have a good management will cause environmental pollution. The waste is still contain high water content and organic ingredients in the form of carbohydrates, protein, and fat. One way to manage the waste market is to process them into liquid compost (organic liquid fertilizer) because it is more quickly absorbed into the ground and quickly utilized directly by plants, and it does not damage the soil and plants. This study aims to produce the organic liquid fertilizer made ??from vegetable market waste and describing levels of nutrients in fertilizers, as well as determine the effect of dose of liquid fertilizer made ??from waste vegetable market on the growth of red spinach plants (Alternanthera ficoides). This study used a randomized block design (RGD) with 4 doses, including 62.5 ml/L/polybag, 93.75 ml/L/polybag, 125 ml/L/polybag  and 156.25 ml/L/polybag, and urea 0.23 g (control) with five replications. Data obtained from phase 1 was the results of elemental analysis of levels of N, P, K and C/N ratio of organic liquid fertilizer. Data obtained from the phase 2 was the height of plant, leaf number, the length of root, as well as red spinach plant biomass which were analyzed with one-way analysis of variants (one-way ANAVA). Organic liquid fertilizer produced in stage 1 had higher levels of nutrient 0.16% N (average), P 0.014%  levels (very low), and 0.25% K (very low). However, the dose of organic liquid fertilizer made ??from different vegetable market waste does not significantly affect plant growth of red spinach (Alternanthera ficoides).